2020
DOI: 10.1126/sciadv.aay6379
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the human heteromeric amino acid transporter b 0,+ AT-rBAT

Abstract: Heteromeric amino acid transporters (HATs) catalyze the transmembrane movement of amino acids, comprising two subunits, a heavy chain and a light chain, linked by a disulfide bridge. The b0,+AT (SLC7A9) is a representative light chain of HATs, forming heterodimer with rBAT, a heavy chain which mediates the membrane trafficking of b0,+AT. The b0,+AT-rBAT complex is an obligatory exchanger, which mediates the influx of cystine and cationic amino acids and the efflux of neutral amino acids in kidney and small int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 62 publications
(69 reference statements)
11
56
0
Order By: Relevance
“…1d-e). This architecture is essentially identical to the recent structures of human b 0,+ AT-rBAT (14), confirming a conserved higher-order assembly (Fig. S6b).…”
Section: Overall Structure Of the Ovine B 0+ At-rbat Complexsupporting
confidence: 83%
See 2 more Smart Citations
“…1d-e). This architecture is essentially identical to the recent structures of human b 0,+ AT-rBAT (14), confirming a conserved higher-order assembly (Fig. S6b).…”
Section: Overall Structure Of the Ovine B 0+ At-rbat Complexsupporting
confidence: 83%
“…Single-particle analysis indicated that the two b 0,+ AT-rBAT subcomplexes are linked together with substantial flexibility, which was also evident in the human complex that showed a blurred TMD map in the consensus 3D refinement (14,15). To account for this flexibility, we performed multi-body refinement (16), taking individual heterodimers as rigid bodies moving relative to each other.…”
Section: The B 0+ At-rbat Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, LAT1 is a potential drug target in cancer but it may also be exploited for drug delivery into the brain. The inward-open conformation cryo-EM structures of the human LAT1-4F2hc complex in its apo state or with the non-specific inhibitor 2-amino-2-norbornanecarboxylic acid (BCH) bound and some eukaryotic homologs of the HAT family were solved [12][13][14][15] . However, structures of LAT1 or other HAT family members in other conformations with or without inhibitors bound are not available yet.…”
Section: Introductionmentioning
confidence: 99%
“…Cryo- and negative stain-electron microscopy (EM) elucidated the supramolecular organization and structures of selected HATs, i.e., of 4F2hc-LAT1 [ 22 , 23 , 24 ], 4F2hc-LAT2 [ 25 , 26 , 27 , 28 ], and rBAT-b 0,+ AT [ 29 ]. Furthermore, the high-resolution cryo-EM structures of 4F2hc-LAT1 [ 22 , 23 ] and rBAT-b 0,+ AT [ 29 ] provided detailed insights into the interactions between the ancillary glycoproteins and the corresponding membrane transporters at the molecular level.…”
Section: Introductionmentioning
confidence: 99%